Implementation of a novel distributed traffic light scheduling strategy in a large scale urban traffic network simulated by VISSIM - Yeo, Terence Zhen Hong (2016)
This report presents a large scale urban traffic simulation model that was based on Jurong East and Jurong West areas of the Jurong Lake District.